Anthropology and medicine - Schmidt, J. M. (British Homeopathic Journal, 1993)
Fundamental reflections on anthropology in medicine lead on to the image of man on which modern, science-orientated medicine is based, followed by that which underlies homœopathy. Hahnemann's concept of man is considered before elucidating the characteristics and differences between the two approaches and their particular position in the theory of medicine. The strict positivism of science essentially reduces the image of man, whilst the teleological approach, renouncing any claim to be able to investigate life itself, permits a phenomenological recognition of man in all his dimensions.
Keywords: Anthropology; Medicine; Science; Teleology; Phenomenology; Homœopathy; Hahnemann